Flexible control of acoustic conditions in a music rehearsal space using airbeds. (February 2021) - Shearer, Douglas; Dance, Stephen; Gomez-Agustina, Luis; Randell, Justin
Abstract: Henry Wood Hall is a former church in central London which was successfully repurposed as an orchestral rehearsal space. However, the trustees of the hall desired a more flexible use of the space and in March 2018 instructed the LSBU Acoustics Group to develop, test and install a flexible solution which would create a balanced acoustic suited to smaller ensembles and voice. This would require the reduction of the reverberation in the hall at low frequencies. The solution should, for a modest budget, be flexible enough to be changed within the hour-long break between sessions. Laboratory tests were undertaken on inflated airbeds in the LSBU reverberation chamber to determine the low-frequency sound absorption potential of these consumer goods. The model with the most promising performance was selected and dependence on inflation was determined. Room acoustic measurements were taken in the hall before and after the airbeds were installed, showing the desired level of reduction in reverberation time in the lower frequency bands.